Total phenolic compounds and antioxidant activity of Brazilian honey: a review (Revista Brasileira Multidisciplinar, 2026)
Honey is characterized by its complex composition, which varies with the raw material origin, such as nectar or honeydew, the bee species, the climatic conditions, the available floral source, and storage conditions. It consists, primarily, of glucose and fructose, but also contains amino acids, phenolic compounds, organic acids, vitamins, minerals, lipids, enzymes, and other phytochemicals. Thus, the objective of this work was, through a literature review, to present relevant information about the antioxidant activity of Brazilian honey, evaluated through different methods, such as: free radical DPPH (2,2-diphenyl-1-picryl-hydrazyl), ABTS (2,2-azinobis (3-ethylbenzothiazoline-6-sulfonic acid)), and FRAP (Ferric Reducing Antioxidant Power). The websites Science Direct, Web of Science, SciELO, and the CAPES Periodicals Portal were used for the bibliographic research. The analysis of the articles indicated that the antioxidant activity of the honey samples varies considerably depending on the flowering of origin, the producing species, and the geographic and environmental conditions. Also, the highest antioxidant activities were observed for the samples that presented the highest levels of total phenolic compounds (TPC).
Keywords: honey; TPC; antioxidants